2013
DOI: 10.1111/jspn.12032
|View full text |Cite
|
Sign up to set email alerts
|

Using Orem's self‐care model for asthmatic adolescents

Abstract: Applying Orem's self-care model increased the self-care skills of adolescents with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
4
22
1
2
Order By: Relevance
“…The current study findings were consistent with those of the study by Altay et al on the effect of the Orem model on self-care in the adolescents with asthma (12). In addition, Matyt reported that QOL and knowledge of the disease in 10-to 14-year-old individuals promoted after intervention, using the Orem model, which confirmed the current study findings (20).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current study findings were consistent with those of the study by Altay et al on the effect of the Orem model on self-care in the adolescents with asthma (12). In addition, Matyt reported that QOL and knowledge of the disease in 10-to 14-year-old individuals promoted after intervention, using the Orem model, which confirmed the current study findings (20).…”
Section: Discussionsupporting
confidence: 83%
“…Altay et al studied the effect of the Orem model on self-care in the adolescents with asthma. They taught the proper use of medication, exercise techniques, use of action plans, careful diet, and protection against stimulants that resulted significant difference in the intervention group, compared with pre-intervention (12). In addition, Tangarayasap et al revealed that the control of selfcare behaviors in patients with asthma improves following the Orem model intervention (13).…”
Section: Introductionmentioning
confidence: 99%
“…A short follow‐up time was the major limitation of most of the studies (n = 20). The remaining 15 studies used an adequate follow‐up time ranging from three to six months.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐six papers focussed on strategies to support self‐management and prevention , through education ( n = 23) or self‐monitoring ( n = 3). Educational strategies involved asthma ( n = 10) , diabetes ( n = 5) , cerebral palsy ( n = 3) , HIV ( n = 3) , epilepsy ( n = 2) and leukaemia ( n = 1) . Studies employed a variety of educational methods (e.g.…”
Section: Resultsmentioning
confidence: 99%